Sewer ductwork crossings with obstacles - Mokrzycka – Olek, Aleksandra (Instal, 2021)
This paper presents the solutions for crossing of sewer ductwork with pre-existing obstacles (like rivers, ditches, canals, sewer networks). The selection of an optimum solution usually requires consideration of various criteria, which may include the vertical drop between the sewer ducts and the elevation datum of the obstacle to be crossed, and profitability considerations of the solution. A general practice for design calculations of hydraulic siphon crossings is selected and discussed.